2002
DOI: 10.1176/appi.ajp.159.9.1548
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Mental Health Care Among U.S. Children: Variation by Ethnicity and Insurance Status

Abstract: These findings reveal that most children who need a mental health evaluation do not receive services and that Latinos and the uninsured have especially high rates of unmet need relative to other children. Rates of use of mental health services are extremely low among preschool children. Research clarifying the reasons for high rates of unmet need in specific groups can help inform policy and clinical programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
925
11
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,396 publications
(970 citation statements)
references
References 41 publications
29
925
11
5
Order By: Relevance
“…Studies showed that young people nowadays are more worried than the equivalent past generations [18][19][20] . Large numbers of young people have been diagnosed to have conditions such as attention deficit hyperactivity disorder (ADHD) 2,3 .…”
Section: Results A) Children and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that young people nowadays are more worried than the equivalent past generations [18][19][20] . Large numbers of young people have been diagnosed to have conditions such as attention deficit hyperactivity disorder (ADHD) 2,3 .…”
Section: Results A) Children and Mental Healthmentioning
confidence: 99%
“…They are challenging themselves with increased stress on education and self-control. Thus, currently there are several psychological disorders among young people such as overthinking and worrying, sleeping problems, hopelessness and stress [19][20][21] . Mental health disorders among children has been shown to be common in the west, and over the world.…”
Section: Results A) Children and Mental Healthmentioning
confidence: 99%
“…However, as multilevel models of health disparities emphasize, health service use is affected by many interacting factors. Race/ethnic disparities in mental health service use are likely attributed primarily to factors such as socioeconomic factors [8], family help-seeking attitudes and beliefs [37,38], and funding or policy level factors [39]. Emerging support for the significant impact of funding level factors comes from studies demonstrating that race/ethnic disparities in unmet need decreased when insurance coverage is expanded in programs such as SCHIP (given that race/ethnic minority children are over-represented in the populations affected by these expansions) [40].…”
Section: Discussionmentioning
confidence: 99%
“…While there is unmet need for mental health care for all children, numerous studies indicate that unmet need is significantly greater for racial and ethnic minority youth compared to non-Hispanic White youth [6][7][8]. Evidence suggests that African American, Latino, and Asian American youth are less likely to enter mental health care and even after entering care, youth from racial/ethnic minority groups obtain fewer and/or less intensive services [7,11,12].…”
Section: Racial/ethnic Disparities In Children's Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation